The Effectiveness of E-Learning Management Through Online Learning Information Systems : An Integrative Approach Model - Nathalia, Dessy Kurnia; Rosyidi, Unifah; Cahyana, Ucu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the effectiveness of e-learning management through online learning information systems calledÂ siberingÂ at the Faculty of Economics, Jakarta State University. The research used a qualitative approach using the case study. Determination of informants in this study using purposive and snowball techniques. Informants in the research were lecturers, students, and e-learning administrators. Data collection techniques in qualitative research were carried out in natural conditions, using primary sources (directly providing data) and observation, interview, documentation, and triangulation methods. The data analysis technique in this study was the data analysis of the Miles and Huberman models, including data collection, data reduction, data display, and conclusion/verification. The results of the data analysis concluded thatÂ sibering had a positive and effective impact on the implementation of e-learning. The results of the system approach model analysis concluded that the learning objectives and the preparation of learning plans were by university standards. The QAIT approach model includes learning system governance that refers to quality operational standards, and the Kirkpatrick approach model includes program evaluations taken from learning outcomes and student satisfaction, which has shown changes in student graduation rates in each course.